Pengaruh Harga dan Kualitas Produk terhadap Kepuasan Pembelian Produk Kosmetik Skintific: Studi Kasus pada Mahasiswa FEBI INSAN Binjai - Adinda Umi Choirani; Sri Herlina; Rizky Fatmawati (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the influence of price and product quality on consumer satisfaction in purchasing Skintific cosmetic products among students of FEBI INSAN Binjai. The research employed a quantitative approach using survey methods and statistical analysis through multiple linear regression. Data were collected from 100 respondents using questionnaires distributed to students who had used Skintific products. The findings indicate that product quality has a positive and significant effect on purchase satisfaction, while the price variable shows a positive but relatively weaker influence. Simultaneously, price and product quality significantly affect consumer satisfaction. The coefficient of determination analysis reveals that the two independent variables contribute 7.8% to consumer satisfaction, while the remaining percentage is influenced by other factors outside this study. These findings suggest that improving product quality and maintaining appropriate pricing strategies are important factors in increasing consumer satisfaction with cosmetic products among university students.